1996
DOI: 10.1055/s-2007-972820
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Running Economy and Temporal EMG Characteristics of Bi-Articular Leg Muscles

Abstract: Relationships between running economy (RE; submaximal VO(2) for a given running speed) and the temporal EMG characteristics of bi-articular leg muscles were quantified in a group of well-trained runners. Nine subjects completed three test sessions: a determination of maximal aerobic demand (VO(2)max); an accommodation session at the experimental speed of 4.13 m.s(-1) and a session during which EMG and RE data were collected simultaneously at the experimental speed of 4.13 m.s(-1) Measures of muscle onset, on-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 0 publications
8
30
0
2
Order By: Relevance
“…The dierence between the least and most economical subjects expressed as a percentage of the mean RE, 26.5%, also was consistent with results of previous studies (Conley and Krahenbuhl 1980;Heise et al 1996;Martin and Morgan 1992). There existed no distinct pattern between subjects' _ V O 2peak and their RE as was veri®ed by the poor correlation between these two variables (r=±0.08).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The dierence between the least and most economical subjects expressed as a percentage of the mean RE, 26.5%, also was consistent with results of previous studies (Conley and Krahenbuhl 1980;Heise et al 1996;Martin and Morgan 1992). There existed no distinct pattern between subjects' _ V O 2peak and their RE as was veri®ed by the poor correlation between these two variables (r=±0.08).…”
Section: Resultssupporting
confidence: 90%
“…ámin ±1 ] and the magnitude and range of RE for the sample [(mean RE 44.6 (SD 3.3) ml O 2 ákg ±1 ámin ±1 ] were typical of those which have been reported previously for similar speeds (Conley and Krahenbuhl 1980;Heise et al 1996;Williams and Cavanagh 1987). The dierence between the least and most economical subjects expressed as a percentage of the mean RE, 26.5%, also was consistent with results of previous studies (Conley and Krahenbuhl 1980;Heise et al 1996;Martin and Morgan 1992).…”
Section: Resultssupporting
confidence: 78%
“…They also noted a trend mentioned is to increase muscle activation time synchronizing can improve the economics of the operation. They assume that a large number of muscle fibers are activated simultaneously may cause joints stiffen, it would be involved in muscle movement and better recovery elastic potential energy, thereby improving the operation of the economy [14] . Other studies have found that the greater the elastic tissue while running the role, the more economic action [15] .…”
Section: Economic Action Forms the Main Component Of Acting And Movementmentioning
confidence: 99%
“…Ces deux résultats pouvant être expliqués par une action de « griffé » préalable à la phase d'appui chez les coureurs entraînés à la course. Dans un autre domaine, Heise et al (1995) ont centré leurs investigations sur les relations entre le coût énergétique de l'athlète et le niveau d'activité musculaire de certains muscles. En course, cette notion de coût énergétique exprime le rapport entre la dépense énergétique (en mlO2.mn-1.kg-1) et la vitesse de déplacement (en m.s-1 ou en km.h-1).…”
Section: Influence De L'expertise Sur Le Niveau D'activité Musculaireunclassified
“…Plus ce rapport est faible, plus le sujet est économique. Heise et al (1995) mentionnent que les durées de coactivité entre les muscles bi-articulaires pendant les phases d'appui et d'oscillation ont une influence sur le coût énergétique. Kyrölaïnen et al (2001), observent également une augmentation de coactivité entre agoniste/antagoniste (VL et BF d'une part, Ga et TA de l'autre) qui aboutirait à l'augmentation de la raideur du genou et de la cheville au début de la phase de contact.…”
Section: Influence De L'expertise Sur Le Niveau D'activité Musculaireunclassified